A Formal Analysis of Diagnosis and Diagnostic Reasoning - Weber, Erik; Provijn, Dagmar (Logique et Analyse, 1999)
Diagnostic reasoning may relate to an established fault in a system or in an individual. With respect to systems, three types of diagnosis are distinguishable: non-explanatory, weak explanatory and strong explanatory. The latter are defined, illustrated and their respective functions are described. The reasoning process for the construction of non-explanatory diagnoses is analysed and we propose two adaptive logics that are adequate tools for modelling this kind of diagnostic reasoning. We also discuss (weak and strong) explanatory diagnostic reasoning and show that it can be divided in three stages. The modelling of each stage requires a different adaptive logic. With respect to individuals, we show that non-explanatory diagnoses do not occur. The earlier findings for explanatory diagnostic reasoning may be adopted.